The Essence of Mechanical Losses and Their Size, Processes of Friction, Lubrication and Wear in Engine Assembly (Czech Journal of Multidisciplinary Innovations, 2022)
Parameters of the dependence of indicators of the technical condition of the engine and oil on the volume of oil added, clarifying and allowing to determine the engine resource and operating time before changing the oil. Parameters of the regime for maintaining the functional state of the lubrication system of forced engines in operation, differing in the frequency and volume of adding oil, which make it possible to exclude extreme lubrication modes.